Estudo de mecanismos dependentes e não dependentes do receptor MAS na potenciação do efeito hipotensor da Bradicinina pela angiotensina (1-7) - Renata Dutra de Paula (2011)
Ang-(1-7) potentiates the hypotensive effect of bradykinin (BK) in normotensive and hypertensive rats. Ang-(1-7) specific antagonists, A-779 or [D-Pro7]-Ang-(1-7), prevented the BK potentiation in rats. Ang-(1-7) effects are mainly mediated by Mas receptor. Mas codes for a G protein-coupled receptor that is implicated in Ang-(1-7) signaling. We evaluate the role of Mas receptor in the potentiation of BK hypotensive effect by Ang-(1-7), Ang-(2-7), Ang-(3-7) or Ala-Ang(1-7) in FVBN and Black C56 mice, WT or Mas-KO female mice. The hypotensive effect of bolus injections of BK (40 ng) combined with different doses of each peptide (80, 160 and 320 ng) were compared to the effect of single doses of BK alone (40 and 80 ng). The same protocol was performed in mice pre-treated with Captopril and L-NAME. In other group, we evaluated the effect of Ang-(1-7) antagonist [D-Pro7]Ang-(1-7) combined to Ang-(1-7) and BK in bolus injections. Ang-(1-7) or Ang-(1-7) related peptides alone did not change MAP but significantly potentiated the hypotensive effect of BK in WT mice. Ang-(1-7) (160 ng) transformed the effect of a single dose of BK (40 ng) to the effect of its double (80 ng) when the experiments were performed either in Black C56 or FVBN WT mice but it was not significant in Mas-KO mice, which was the most important finding of this study. L-NAME pre-treatment of mice attenuated the BK potentiation of Ang-(1-7). In summary those results have demonstrated that potentiation of the hypotensive effect of BK of Ang-(1-7) relies on Mas receptor and NO synthesis and releasing mechanisms